Newly-Engineered Materials for Bio-Imaging Technology: A Focus on the Hybrid System of Ultrasound and Fluorescence - Pei, Yanbo; Wei, Ming-Yuan (Frontiers in Bioengineering and Biotechnology, 2019)
As an emerging technique, ultrasound-modulated fluorescence (UMF) or ultrasound switchable fluorescence (USF) bioimaging has shown promising features to produce deep-tissue and high-resolution fluorescence imaging for biomedical research and health diagnosis. The success of UMF or USF heavily relies on the design of their contrast agents (CAs). We herein surveyed recent advances in the development of such unique CAs, including configuration, mechanism, stability, sensitivity, and selectivity. Meanwhile, UMF or USF instrumentation has emerged as developmental breakthrough technologies to existing bio-imaging techniques. The best performance of UMF or USF bio-imaging requires an interactive response between CAs and the instrument. In this review, the description of UMF or USF instrumentation are also included for clarification and better understanding. Finally, the UMF and USF’s performance in bioimaging is evaluated based on signal-to-noise ratio, resolution, imaging depth and speed, using photoacoustic imaging (PAI) as a standard, a well-developed technique of hybrid bio-imaging. Unlike PAI, UMF or USF is still in its early stage. Although results demonstrated a proof-of-concept landmark being reached, significant efforts are needed to improve the performance of UMF or USF.